(untitled) (The Review of Diabetic Studies, 2024)
Background: The existence of a malignant tumor is one particular instance of how the illness and anticancer treatment profoundly disrupt homeostasis and metabolism. Thus, increasing weight loss and varied levels of malnutrition are common signs of the onset of a neoplastic disease and represent a significant issue in oncology. Goal of the research. One of the variables for the outcomes of surgery, chemotherapy, or radiation therapy to deteriorate is poor nutritional condition, which is typically linked to cancer. This study set out to evaluate the dietary health of CRC patients who were eligible for chemotherapy. Methods and Materials: City Hospital (KAMC), Mecca, Saudi Arabia. From January 2024 to April 2024, all patients with colorectal cancer who visited the outpatient Surgery and Oncology department for the first time were invited to take part in the study. In order to determine the nutritional state of patients with colorectal cancer both before and after surgery and other therapies, an English questionnaire was created specifically for data collection. It was piloted, tested, and adjusted as necessary. a face-to-face interview with every patient who has been diagnosed with colorectal cancer. The interview lasted between twenty and thirty minutes (Karlsson et al., 2009). Results: Thirteen female patients and seventeen male patients made up the total number of participants. Of the patients, 30% lacked literacy, 20% had an elementary or intermediate degree, 23.3% had a high school diploma, and 26.7% had a bachelor’s degree or above. 90% of the patients were deemed well-nourished at the time of the initial assessment, while 100% had moderate levels of malnutrition. Out of the 46 patients who were assessed following surgery, one (4%) displayed evidence of severe malnutrition, the others had signs of moderate malnutrition, and the remaining patients were deemed to be well-nourished. Considering that three of the four patients who had displayed malnutrition symptoms on the initial evaluation continued to exhibit same scores after being admitted, there were four additional cases of malnutrition throughout hospitalization. Conclusion: Colorectal cancer Patients definitely have a serious nutritional issue, which undoubtedly affects how their illness develops, how long they stay in the hospital following surgery, and how long they need to receive additional care. The majority of cancer patients need additional nutritional care since they are thought to be at risk for malnutrition. To find weight-loss patients early in the care pathway when they first reach the secondary care system, nutritional screening would be helpful in this group prior to surgery.